2015
DOI: 10.1177/1403494815576787
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of acute gastrointestinal illness in Sweden

Abstract: Aims: The aim of this study was to estimate the self-reported domestic incidence of acute gastrointestinal illness in the Swedish population irrespective of route of transmission or type of pathogen causing the disease. Previous studies in Sweden have primarily focused on incidence of acute gastrointestinal illness related to consumption of contaminated food and drinking water. Methods: In May 2009, we sent a questionnaire to 4000 randomly selected persons aged 0–85 years, asking about the number of episodes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
5
7
3
Order By: Relevance
“…This is substantially higher than the 0.4 episodes per year reported by these elite cross-country skiers. However, similar to the current study, Hansdotter et al 21 reported 0.3–0.4 events of acute gastrointestinal illness per person-year in Sweden in the period 2008–2009. Determining precise incidence rates of RTI and GII in the general population is challenging, since many may not report mild cold and influenza symptoms to the doctor.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is substantially higher than the 0.4 episodes per year reported by these elite cross-country skiers. However, similar to the current study, Hansdotter et al 21 reported 0.3–0.4 events of acute gastrointestinal illness per person-year in Sweden in the period 2008–2009. Determining precise incidence rates of RTI and GII in the general population is challenging, since many may not report mild cold and influenza symptoms to the doctor.…”
Section: Discussionsupporting
confidence: 88%
“…However, in the current study, sex was not significantly associated with either symptom incidence or duration, nor was age a significant predictor of symptom incidence. Although previous studies have found that age influences the incidence rates of acute GII21 and RTIs,8 the age range in the current study was comparatively narrow (18–34 years). Furthermore, since there were no significant differences between the recruit and senior team, the number of years of athletic training, within the range studied, does not appear to influence the frequency of acute gastrointestinal and respiratory tract symptoms in this population.…”
Section: Discussioncontrasting
confidence: 63%
“…In one UK study, when both definite and possible cases were included, the AGI incidence increased to 523/1000 person-years [1], higher than the Swedish AGI incidence estimate. A study estimating AGI incidence in Sweden using a different methodology obtained a similar estimate, validating our result [14]. It is also possible that the overall AGI incidence has increased since cohort studies with a similar methodology were carried out in The Netherlands and the UK (1999 and 2009); in the UK, AGI incidence increased by 40% between the mid-1990s and 2009 [1].…”
Section: Discussionsupporting
confidence: 84%
“…In Sweden, one previous retrospective study attempted to measure community incidence of AGI. It estimated AGI incidence at 310/1000 person-years in 2009 [14], without assessing the AGI costs to society. In 2013, The Public Health Agency of Sweden invited 34 970 Swedish residents up to the age of 85 years, selected using random age-stratified sampling to join Hälsorapport, a prospective, population-based cohort with several objectives, among which included measuring the incidence of a range of symptoms in the Swedish population via weekly health status reports.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea only was the predominant symptom profile of cases (55.9% and 61.1%, resp., for the two case definitions); this result falls between other studies, reporting a higher proportion in Germany (78%) and Denmark (64%) and lower proportions in Sweden, Italy, and Chile (30–40%) [ 6 , 12 , 14 , 35 , 39 ]. The proportion of diarrheal cases with bloody diarrhea (9.9%) was higher than that in other countries (3-4%) [ 5 , 12 , 13 , 35 ].…”
Section: Discussioncontrasting
confidence: 45%